Effects of nitrogen, phosphorus and potassium deficiencies on growth and development of Globba rosae Gagnep. - Soraya Ruamrungsri (2018)
The effects of N, P and K deficiencies on growth, development and nutrient status of Globba rosae were investigated using soilless culture. Rhizomes of Globba rosae Gagnep. were planted in sand medium. After emergence, plants were supplied with nitrogen (N), phosphorus (P) or potassium (K) deficient solutions, compared with a complete nutrient solution (control treatment) and nutrient-free solution (only tap water). Plants were sampled at flowering (7-8 weeks after planting, WAP) and before dormancy stages (12 WAP) to determine the nutrient contents of the aerial and underground parts. Nutrient deficiency symptoms were observed in -N, -P and -K treatments. Leaf of -N treatment was small and yellowish green, the pink bract was pale and had no floret. For P and K deficient symptoms, leaves were small, floral bracts were pale. Plant height, number of leaves per plant, number of plants per cluster, number of racemes per plant in nutrient deficiency treatments were reduced. Days to flower was retarded compared with control treatment. The optimum levels of nitrogen, phosphorus and potassium in nutrient solution for growth of Globba rosae were 100, 100 and 200 mg l-1, respectively.